Enhancing the Optoelectronic Performance of Perovskite Solar Cells via a Textured CH3NH3PbI3 Morphology. (3rd January 2016) - Pascoe, Alexander R.; Meyer, Steffen; Huang, Wenchao; Li, Wei; Benesperi, Iacopo; Duffy, Noel W.; Spiccia, Leone; Bach, Udo; Cheng, Yi‐Bing
Abstract : Perovskite‐based solar cells are generally assembled as planar structures comprising a flat organoammonium metal halide perovskite layer, or mesoscopic structures employing a mesoporous metal‐oxide scaffold into which the perovskite material is infiltrated. To present, little attention has been directed toward the texturing of the perovskite material itself. Herein, a textured CH3 NH3 PbI3 morphology formed through a thin mesoporous TiO2 seeding layer and a gas‐assisted crystallization method is reported. The textured morphology comprises a multitiered nanostructure, which allows for significant improvements in the light harvesting and charge extraction performance of the solar cells. Due to these improvements, average short‐circuit current densities for a batch of 28 devices are in excess of 22 mA cm −2, and the maximum recorded power conversion efficiency is 16.3%. The performance gains concomitant with this textured CH3 NH3 PbI3 morphology provide further insights into how control of the perovskite microstructure can be used to enhance the cell performance. Abstract : A textured CH3 NH3 PbI3 morphology for perovskite‐based solar cells is presented. The textured morphology exhibits enhanced light harvesting and charge separation properties. The highest measured power conversion efficiency is 16.3%.